KONTRIBUSI FATIGUE INDEX TERHADAP KINEMATIC MOVEMENT FREE THROW DALAM PERMAINAN BOLA BASKET - Yuvi, Setia Dwi Putra (2018)
Free throw adalah tembakan yang dilakukan karena mendapatkan pelanggaran pada saat memasukkan bola kearah ring dengan nilai dalam satu kali tembakan adalah satu. Penelitian ini bertujuan untuk mengetahui hubungan dan kontribusi Center of mass, angle of elbow joint, angular velocity of elbow joint, angle of wrist joint, angular velocity of wrist joint, release height of the ball, angel release of ball dan angel release of upper armterhadap hasil lemparan free throw yang dipengaruhi oleh fatigue index. Metode yang digunakan dalam penelititan ini adalah Deskriptif korelasional, sampel 10 orang berusia 15-17 tahun. Analisis kinematik menggunakan software kinovea, kamera Sony 32GB HDR-PJ540,polar dan tes RAST, analisis data menggunakan SPSS versi 20 dengan pengujian korelasi dan regresi. Hasil penelitian ini menyimpulkan dari 8 indikator hanya satu yang memiliki hubungan dan kontribusi yang signifikan terhadap hasil lemparan free throw yaitu angular velocity of wrist joint. Kesimpulan dari penelitian ini yaitu dapat dijadikan suatu rujukan untuk ilmu kepelatihan bahwa betapa pentingnya melatih kinematic movement atlet basket dalam lemparan free throwdi saat kondisi atlet kelelahan.;--- Free throw is a shot that is done because it gets a foul on when entering the ball towards the ring with the value in one shot is one. This study aims to determine the relationship and contribution of Center of mass, angle of elbow joint, angular velocity of elbow joint, angle of wrist joint, angular velocity of wrist joint, release height of the ball, angel release of ball and angel release of upper arm against free throw throws that are affected by the fatigue index. The method used in this study is a correlational descriptive, a sample of 10 people aged 16-18 years. Kinematic analysis using kinovea software, Sony 32GB HDR-PJ540 camera, polar and RAST test, data analysis using SPSS version 20 with correlation and regression testing. The results of this study concluded from 8 indicators only one that has a significant relationship and contribution to the result of free throw throw is angular velocity of wrist joint. The conclusion of this research is that it can be used as a reference for the science of coaching that how important to train kinematic movement basketball athlete in throw free throw at the condition of fatigue athlete.